(untitled) - Randall, John Herman (New York, 1940)
From the medieval worldview to the modern outlook, this work presents a sweeping intellectual history in one volume. The emphasis is on ideas in their historical setting, on how modes of thought emerge, grow, influence and react to one another, and die. The result is a grand synthesis of the main currents in western thought, bringing together religion, philosophy, politics, science, economics, literature and the arts, and the social and behavioral sciences- all the diverse systems man has devised in his effort to understand, interpret, and shape human experience.
Keywords: Philosophy, Modern,Philosophy, Medieval,Triết học, hiện đại,Triết học, thời trung cổ; History,Lịch sử